2017
DOI: 10.18196/agr.3248
|View full text |Cite
|
Sign up to set email alerts
|

Farming Performance of Rice Farmer for Sustainable Agriculture and Food Security in West Kalimantan

Abstract: For more than three decades, domestic rice production was not able to meet its growing demand and showed in poor performance. This research aims to analyze the performance of rice farming in West Kalimantan. The research was conducted using descriptive methods through interviews. The data was analyzed to describe farmer personal character, skill and knowlwdge, risk analysis, and technical efficiency employing stochastic frontier model. This study proved that farmer had 3 to 6 years of pupilage attainment; used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
(15 reference statements)
0
11
0
6
Order By: Relevance
“…Namun, pengelolaan usahatani oleh kelompok tani di Rasau Jaya, Kalimantan Barat khususnya kelompok tani "Sumber Lestari" menunjukkan kinerja keterampilan manajerial petani yang masih sangat rendah yang dibuktikan dengan sebagian besar capaian efisiensi teknis hanya sebesar 60-70%. [1] Disamping itu, petani dalam kelompok tani umumnya hanya secara intuitif menekankan pada aspek biaya dan penerimaan usahatani untuk tujuan pembiayaan input produksi dan tidak mampu membuat keputusan usahatani yang optimal. Kondisi ini dilatarbelakangi oleh tidak adanya data usahatani (farm record).…”
Section: Pendahuluanunclassified
See 3 more Smart Citations
“…Namun, pengelolaan usahatani oleh kelompok tani di Rasau Jaya, Kalimantan Barat khususnya kelompok tani "Sumber Lestari" menunjukkan kinerja keterampilan manajerial petani yang masih sangat rendah yang dibuktikan dengan sebagian besar capaian efisiensi teknis hanya sebesar 60-70%. [1] Disamping itu, petani dalam kelompok tani umumnya hanya secara intuitif menekankan pada aspek biaya dan penerimaan usahatani untuk tujuan pembiayaan input produksi dan tidak mampu membuat keputusan usahatani yang optimal. Kondisi ini dilatarbelakangi oleh tidak adanya data usahatani (farm record).…”
Section: Pendahuluanunclassified
“…Disamping itu, petani juga menghadapi kendala internal seperti motivasi, pengalaman usahatani dan luas lahan garapan, pendidikan, karakateristik manajerial serta faktor eksternal seperti sarana dan prasarana. [1] [2] [3] Kondisi ini dilatarbelakangi oleh tingkat pemahaman petani terkait aspek manajemen pembiayaan dan resiko usahatani yang juga rendah. Hal tersebut diperkuat dengan adanya temuan bahwa sebagian besar penguasaan lahan oleh sebagian besar petani dalam kelompok tani adalah 0,25-1,25 ha dan hanya sebagian kecil yang lebih dari 2,25 ha.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Due to the increasing population, the demand for rice will continue to grow. Nurliza et al (2017) reported that approximately 90% of the total population of Indonesia consume rice as staple food. Unfortunately, for almost three decades, domestic rice production has been insufficient in meeting the demand that continues to grow.…”
Section: Introductionmentioning
confidence: 99%